Just add all of them up and there is your answer I just added it but I want u to work it out to..
<em>A</em> - <em>B</em> = (10<em>i</em> - 2<em>j</em> - 4<em>k</em>) - (<em>i</em> + 7<em>j</em> - <em>k</em>)
<em>A</em> - <em>B</em> = 9<em>i</em> - 9<em>j</em> - 3<em>k</em>
|<em>A</em> - <em>B</em>| = √(9² + (-9)² + (-3)²) = √189 = 3√19
..........................................................
You need to set their position functions equal to one another and so for the time t when that is true. That is when the tiger and the deer are in the same place meaning the tiger catches the dear
Xdear= 2t+15 deer position function.
(I integrated the velocity function )
To get the Tigers position function you must integrate the acceleration twice. This becomes
Xtiger=t^2
Now t^2=2t+15
Time t is when the tiger catches the deer
t^2-2t-15=0
(t-5)(t+3)=0 factored
t=5s is the answer you use (t=-3 is a meaningless solution)